Natriuretic Peptide and High-Sensitive Troponin T Concentrations Correlate with Effectiveness of Short-Term CPAP in Patients with Obstructive Sleep Apnea and Coronary Artery Disease - Strehmel, Ralf (Clin Med Insights Circ Respir Pulm Med, 2016)
The risk of cardiovascular complications is increased in patients with obstructive sleep apnea (OSA). Continuous positive airway pressure (CPAP) is the most effective way to treat clinically significant OSA. We hypothesized that the concentrations of the cardiac risk markers N-terminal brain natriuretic peptide (NT-proBNP) and high-sensitive troponin T (hs-TropT) correlate with the effectiveness of CPAP therapy in patients with OSA and coexisting coronary artery disease (CAD). Twenty-one patients with severe OSA and coexisting CAD (group 1) and 20 control patients with severe OSA alone (group 2) were treated with CPAP and monitored by laboratory-based polysomnography. NT-proBNP and hs-TropT levels were measured before and after CPAP. Apnea–hypopnea index (AHI) and oxygen desaturation were similar in both groups. In group 1, hs-TropT levels correlated with AHI and oxygen desaturation upon CPAP. Elevated NT-proBNP levels in group 1 were significantly reduced by CPAP. NT-proBNP levels correlated with AHI and showed negative correlation with ST-segment depression. No such correlations were found in group 2. CPAP has the potential to normalize elevated NT-proBNP serum levels in patients with severe OSA and coexisting CAD. Levels of NT-proBNP and hs-TropT correlated with AHI and oxygen desaturation.